It is Only a Matter of Style: Hollywood and the Myth of American Cultural Influence in Poland - Lewandowski, Tadeusz (Stylistyka, 2006)
The paper deals with the perceived hegemony of American mass culture in Poland and its effects on young people. It is argued that the supposed “Americanization” of Poland through Hollywood films does not constitute any serious threat to Polish national identity, and in fact has little to do with any genuine American cultural influence. Rather, it amounts to the passing adoption of American styles. Explaining that Hollywood is an internationally owned and operated force that works more to appeal to the tastes of the worldwide audience than America’s, it is concluded that the globalization of America cinema is more a threat to the U.S.A.’s national identity than that of other countries. Additionally, the fact that many Americans such as right-wing politicians and conservative Southerners and Midwesterners have viewed Hollywood antagonistically from its inception, indicates the degree to which it should not be considered as representative of American culture or the nation as a whole. Likewise, the content of Hollywood’s films has almost nothing to do with the reality of the country it happens to rest in. To illustrate the point that Poland does not suffer from Americanization, American and Polish national characteristics are detailed to demonstrate the vast differences between the world views and cultures of these two nations and peoples. Ultimately, it is suggested that there has been no significant internal cultural impact on Polish youth due to contact with American entertainment, other than on the surface in the form of fashion and appearance. Also, they are becoming more and more derisive of American mass culture as time passes. Therefore, core Polish attitudes have not become more American and Polish culture, which has survived so much m the past, has very little to fear from the vapid Hollywood fantasy land a continent away.